Evaluating myelophil, a 30% ethanol extract of Astragalus membranaceus and Salvia miltiorrhiza, for alleviating fatigue in long COVID: a real-world observational study - Joung, Jin-Yong; Lee, Jin-Seok; Choi, Yujin; Kim, Yoon Jung; Oh, Hyeon-Muk; Seo, Hyun-Sik; Son, Chang-Gue (Frontiers in Pharmacology, 2024)
Background: Persistent post-infectious symptoms, predominantly fatigue, characterize Long COVID.This study investigated the efficacy of Myelophil (MYP), which contains metabolites extracted from Astragalus membranaceus and Salvia miltiorrhiza using 30% ethanol, in alleviating fatigue among subjects with Long COVID.In this prospective observational study, we enrolled subjects with significant fatigue related to Long COVID, using criteria of scores of 60 or higher on the modified Korean Chalder Fatigue scale (mKCFQ11), or 5 or higher on the visual analogue scale (VAS) for brain fog. Utilizing a single-arm design, participants were orally administered MYP (2,000mg daily) for 4 weeks. Changes in fatigue severity were assessed using mKCFQ11, Multidimensional Fatigue Inventory (MFI-20), and VAS for fatigue and brain fog. In addition, changes in quality of life using the short form 12 (SF-12) were also assessed along with plasma cortisol levels.Results: A total of 50 participants (18 males, 32 females) were enrolled; 49 were included in the ITT analysis with scores of 66.9±11.7 on mKCFQ11 and 6.3±1.5 on the brain fog VAS. After 4 weeks of MYP administration, there were statistically significant improvements in fatigue levels: mKCFQ11 was measured at 34.8±17.1 and brain fog VAS at 3.0±1.9. Additionally, MFI-20 decreased from 64.8±9.8 to 49.3±10.8, fatigue VAS dropped from 7.4±1.0 to 3.4±1.7, SF-12 scores rose from 53.3±14.9 to 78.6±14.3, and plasma cortisol levels also elevated from 138.8±50.1 to 176.9±62.0/mL. No safety concerns emerged during the trial.Current findings underline MYP's potential in managing Long COVID-induced fatigue.However, comprehensive studies remain imperative.